Light and scanning electron microscopic investigation of postnatal development of vallate papillae in the white laboratory mice - Toprak, Burhan; Yilmaz, Sadik (Ataturk Universitesi, 2016)
The aim of this study was to investigate postnatal changes that might occur on vallate papilla of laboratory mice by using light and scanning electron microscopy (SEM). Eight groups were formed for 1, 15, 30, 60, 90, 120, 150 and 180 days old mice and 8 mice were used in each group. Micrometric measurements of vallate papilla which was located median line on dorsal surface of radix area of tongue showed that development of this papilla was very fast for first 15 days period. After then, increases in length and width of papilla and depth and width of trench were slowed down but development continued to 120th day. First mature taste buds which had taste pores were seen on 4th the day of the age. Increase of length and width of taste buds continued by 90th day, increase of number of taste buds continued by 30th days. Trench wall surface area increased 136% in first 15 days period, after this period by 90th day it develop in parallel to the age. In the structure of scanning electron microscopy of vallate papilla, epithelial cell-margin thickness was evident and had micropits and microridges on the surface cells. As a result, it is detected that vallate papillae developed by 120th day and taste buds developed and became functional in the first 4 days.
Keywords: Electron microscopy (SEM); Mouse-vallate; Papillae-development-scanning